Jewish national autonomy in Lithuania in 1919-1926th - Raimundas Valkauskas (Lietuvos Istorijos Studijos)
After World War I, the problems of the racial, linguistic, and religious minorities were brought to the attention of the Peace Conference of Paris. The Jewish community, through a special delegation, demanded the recognition of the Jews as a "national minority" and brought their influence to protect and safeguard the rights of Jews.